Yeats, Bloom and the dialectics of theory, criticism and poetry - Skelley, Steven J. (1992)
This thesis begins by showing how a strong and subtle challenge to poetry and theories of poetry has been recently argued by writers like Paul de Man and J. Hillis Miller—critics whose ironic linguistic "disfigurations" of lyrical voice have thrown poem and poet into an anti-mimetic free fall, an abyss of bewilderment or undecidability. To its credit, de Manian deconstruction strongly misreads various mimetic approaches to William Butler Yeats, as its corrosive irony empties out theories of imitation. Chapter two explains how New Criticism, biographical, psychoanalytic, and philosophical criticism, all treat Yeats's poetry as a reflection or imitation of some prior being, text, or doctrine; and chapter three how, most recently and energetically, various new historicisms treat his poems as ideological artifacts determined by the world or history, but as artifacts that must seek to change the world in order to have value.